Haven or Heartache? Immigrant Women and the Household - Gannagé, Charlene (Anthropologica, 2022)
At the theoretical level, this paper provides an important corrective to the false polarity of two positions: (a) that women’s position in the household is the locus of their gender oppression; and (b) that the family is essential to working-class survival and solidarity. Drawing on in-depth interviews with immigrant women workers in a Toronto garment factory, the paper focuses on the complex and contradictory aspects of their family experiences. It examines women’s double day of labor in detail, and demonstrates the ways in which immigrant women are both reliant on and oppressed by their position within the household.